2016
DOI: 10.3920/wmj2016.2109
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and mitigation options to manage aflatoxin contamination in food with a climate change perspective

Abstract: Understanding the impact of climate change remains vital for food safety and public health. Of particular importance is the influence of climatic conditions on the growth of Aspergillus flavus and production of their toxins. Nevertheless, little is known about the actual impact of climate change on the issue. Setting up of relevant measures to manage the impact has therefore become a daunting task especially in developing nations. Therefore, this study aimed at providing adaptation and mitigation options to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…The safety of this food is potentially a very significant issue for LMICs because much of it is associated with recognized microbiological and other food-based hazards (for example, meat, fish, and milk-based foods). While the literature is not conclusive on this subject, there is evidence that food safety practices in these areas tend to be weak (Macheka et al 2013;Wambui et al 2016), and that the incidence of foodborne pathogens can be significant (Chahed et al 2006;Beneduce et al 2008;Elgroud et al 2009;Grace et al 2011;Nguyen-Viet et al 2013;Doyle et al 2015).…”
Section: Food Safety Risks In Lmic Domestic Marketsmentioning
confidence: 99%
“…The safety of this food is potentially a very significant issue for LMICs because much of it is associated with recognized microbiological and other food-based hazards (for example, meat, fish, and milk-based foods). While the literature is not conclusive on this subject, there is evidence that food safety practices in these areas tend to be weak (Macheka et al 2013;Wambui et al 2016), and that the incidence of foodborne pathogens can be significant (Chahed et al 2006;Beneduce et al 2008;Elgroud et al 2009;Grace et al 2011;Nguyen-Viet et al 2013;Doyle et al 2015).…”
Section: Food Safety Risks In Lmic Domestic Marketsmentioning
confidence: 99%
“…The extent of climate change on the growth and proliferation of the A. flavus community and potential to produce aflatoxins cannot be ignored. An integrated approach for aflatoxins mitigation measures has been recommended at various levels that take into consideration the volatility of the impacts of climate change (Bandyopadhyay et al , 2016 ; Wambui et al , 2016b ). Furthermore, investigations on the effects of agronomic traits and soil health on aflatoxins that have been studied (Mutiga et al, 2017 ) need to be advanced to a conclusive outcome.…”
Section: Knowledge Gaps and Prioritisation Of Research Effortsmentioning
confidence: 99%
“…Climate change is widely accepted and rises in temperature, increased precipitation and carbon dioxide levels and drought will all have a significant effect on food security (Marroquín-Cardona et al 2014). Furthermore, it is expected that developing countries will bear the greatest impact compared with developed countries (Wambui et al 2016). As described, the most important factors affecting fungal growth are moisture and temperature, however other factors including inoculum concentrations, microbial interactions, insect infestation, physical damage, availability of nutrients and carbon dioxide levels will promote infection and contamination (CAST 2003).…”
Section: Effect Of Climate Change On Aflatoxin Productionmentioning
confidence: 99%
“…Generally, the focus has been on maize, however this information is useful in determining the growth and distribution of the toxigenic strains. In Kenya, it has been estimated that there may be a 59% increase in aflatoxin contamination levels in central and western parts due to increasing temperatures, whereas in eastern and southern regions, contamination will decrease by approximately 45% (Wambui et al 2016). Other studies researching the potential influence of climate change on aflatoxins in maize in the USA (Wu et al 2010) and in Malawi (Warnatzsch et al 2020), concluded that greater contamination with aflatoxins is the likely scenario in the future.…”
Section: Effect Of Climate Change On Aflatoxin Productionmentioning
confidence: 99%